Product Country Image Skincare Korea di Indonesia: Sebuah Tinjauan Literatur - Meylia Adillah; Vidiyana Anggrayni; Tita Rosalia; Mohamad Zein Saleh (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study examines the role of South Korea’s Product Country Image (PCI) in influencing Indonesian consumers’ interest and purchasing decisions toward Korean skincare through a literature review. The findings show that Korea’s PCI acts as a quality signal, leading consumers to perceive Korean skincare as safe, innovative, and effective. These perceptions enhance perceived quality, positive attitudes, and purchase intention. Supporting factors such as the Korean Wave, brand ambassadors, brand image, and electronic word of mouth further strengthen consumer confidence. However, some studies note that brand prestige and ethnocentrism do not always produce significant effects. Overall, Korea’s PCI plays a key role in shaping Indonesian consumer preferences for Korean skincare.